Analisis Kelayakan dan Strategi Pengembangan Usaha Susu Kambing Pasteurisasi pada Harjo Lestari Integrated Farm Pasca Pandemi Covid-19 Di Kabupaten Jember - Vandi, Ryan Maulana Riadi (Universitas Galuh, 2024)
Harjo Lestari Integrated Farm is a sheep and goat farm with one of its business units being the production of dairy goat milk. The business unit was established during the Covid-19 pandemic by taking advantage of the increased demand for milk. Milk is produced from different types of goats. Over time, the demand for milk decreased and this affected the low milk production of pasteurized goats because some of the results of milking were used as fodder, so it became a consideration for the business unit to rearrange the same type of goats in order to boost milk production and produce the same quality milk. Identification of internal and external factors to find out the conditions and constraints of the business unit is expected to be resolved and become an illustration of the formation of recommendations for development strategies. This study aims to determine: (1) financial feasibility; (2) variable cost sensitivity; and (3) business unit development strategy for pasteurized goat milk. The method of determining the area using purposive method. The research method uses descriptive methods and analytical methods. The sampling method used purposive sampling. Methods of data collection is done by interviews, observation and study of documents. Data analysis based on financial feasibility analysis and sensitivity analysis and SWOT analysis. The results of the study (1) positive NPV value of IDR 89,464,840, Net B/C of 3.59, IRR of 60%, payback period of 1 year 10 months 4 days. (2) The pasteurized goat milk business unit is not sensitive to the 30% increase in fuel prices. (3) The SWOT analysis calculation is obtained from an IFAS value of 2.6 and an EFAS value of 2.9 which is in the white area position. So that the pasteurized goat's milk business unit Harjo Lestari Integrated Farm after the Covid-19 pandemic is still financially feasible to run and the development strategy that can be applied is Strength-Opportunities (SO).